2018
DOI: 10.1080/02699931.2018.1495618
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in the emotional modulation of gaze-cuing

Abstract: Gaze-cuing refers to the spontaneous orienting of attention towards a gazed-at location, characterised by shorter response times to gazed-at than non-gazed at targets. Previous research suggests that processing of these gaze cues interacts with the processing of facial expression cues to enhance gaze-cuing. However, whether only negative emotions (which signal potential threat or uncertainty) can enhance gaze-cuing is still debated, and whether this emotional modulation varies as a function of individual diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(64 citation statements)
references
References 73 publications
0
63
1
Order By: Relevance
“…With high-anxious people, it is reported that they have difficulty suppressing processing of threat-related distractors [39]; and this difficulty would result in the large magnitude of the effect with fearful gaze as reported in previous studies [79, 18]. On the other hand, recent research suggested that the magnitude of GCE with fearful gaze did not vary as a function of self-reported trait anxiety [14, 15, 40]. In the present study, we conducted the experiment among an unselected sample of people; therefore, further research is needed to clarify whether participant’s anxiety traits and/or autistic traits [17] relate to the magnitude of the GCE in the saccade response mode with fearful gaze.…”
Section: Discussionmentioning
confidence: 95%
“…With high-anxious people, it is reported that they have difficulty suppressing processing of threat-related distractors [39]; and this difficulty would result in the large magnitude of the effect with fearful gaze as reported in previous studies [79, 18]. On the other hand, recent research suggested that the magnitude of GCE with fearful gaze did not vary as a function of self-reported trait anxiety [14, 15, 40]. In the present study, we conducted the experiment among an unselected sample of people; therefore, further research is needed to clarify whether participant’s anxiety traits and/or autistic traits [17] relate to the magnitude of the GCE in the saccade response mode with fearful gaze.…”
Section: Discussionmentioning
confidence: 95%
“…Work on gaze cueing has provided support for this assumption. For example, Wiese, Wykowska, Zwickel, and Muller [ 48 ] found that when observers believed an agent has intention, larger attention shifts occurred compared to when observers did not have this belief (see also, [ 49 , 50 ]). It is also the case, however, that a face exhibiting fear does not reliably induce greater cueing effects relative to a neutral face [ 16 , 51 , 52 ].…”
Section: Representation Rather Than Functionmentioning
confidence: 99%
“…Joint attention is how we share experiences with others as infants, and is crucial for our social development (Baron-Cohen, 1995; Edwards et al., 2015; Brooks and Meltzoff, 2014; Moore et al., 2014). It is no surprise then that failure to integrate gaze and emotion cues has been reported in individuals with Autism Spectrum Disorder (Uono et al., 2009; De Jong et al., 2008) and is related to poor social functioning (Hayward and Ristic, 2017) and autistic like traits within the general population (McCrackin and Itier, 2018b).…”
Section: Introductionmentioning
confidence: 99%